HARASSMENT OF WOMEN AT WORKPLACE: A QUALITATIVE SURVEY FROM RAWALPINDI AND ISLAMABAD - Wajid Rahim; Dr. Khalid Mahmood; Hina Mahmood Khan; Sehrash Afreen (Review Journal of Social Psychology & Social Works, 2024)
The purpose of this study was to examine how woman are being harassed and teased in organizations. Sexual harassment and pestering in organizations whether it is public or private organizations are a very sensitive and complicated issue. In the context of Pakistan, our society is male dominant. Whether it is household or any organizations male dominance is the culture of our country. The negative effects and stress faced by the victim is also equally important to counter. The organization should help the victims to overcome the pressure by removing the negative effects raised from sexual harassment. The victims of sexual harassment often face lack of confidence. This has been a serious issue since the joining of women as a work force. Every working women should stand up now for her right and fight against the unwilling demands of sexuality and this cruelty. Keywords: Sexual harassment, victims, working women, young, unmarried.